Maya Index dan Kepadatan Larva Aedes aegypti di Kota Ternate, Maluku Utara - Amalan Tomia; Upik Kesumawati Hadi; Susi Soviana; Elok Budi Retnani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Dengue hemorrhagic fever (DHF) is a contagious disease caused by the dengue virus and transmitted through the bite of Aedes aegypti. Information regarding larval habitat is very important for the control of Ae. aegypti. The studied aims to determine the density of Ae. aegypti larvae and maya index in Ternate City. The research conducted in 20 urban villages in Ternate City for 5 months. Survey method used was single larva and any water reservoirs were found larvae of Aedes spp. will be taken as a sample. The purpose of this study to measure the density of Ae. aegypti larvae and maya index in Ternate City. The parameters calculated were Container Index (CI), Breteau Index (BI), House Index (HI), Density Figure (DF), and Maya Index. Based on maya index, 1.990 houses in 20 urban villages in Ternate City included in the medium risk category (78.64%) with CI (43.95%), HI (84.99%) and BI (228.91). Density figure in the high category (DF = 8.7). The study concluded that most of households in the area of study still have the potential for transmission of dengue virus infection.